The placenta as a barrier for toxic and essential elements in paired maternal and cord blood samples of South African delivering women - Rudge, Cibele Vieira Cunha [UNESP]; Rollin, Halina B.; Nogueira, Claudina M.; Thomassen, Yngvar; Rudge, Marilza Vieira Cunha [UNESP]; Odland, Jon O. (Royal Soc Chemistry, 2009)
Environmental toxicants such as metals may be detrimental to foetus and infant development and health because of their physiological immaturity, opportunistic and differential exposures, and a longer lifetime over which disease, initiated during pregnancy and in early life, can develop. The placental mechanisms responsible for regulation of absorption and excretion of elements during pregnancy are not fully understood. The aim of this paper is to assess the correlation for selected toxic and essential elements in paired whole blood samples of delivering women and cord blood, as well as to evaluate the placental permeability for selected elements. Regression analyses used to assess this correlation in 62-paired samples of maternal and cord whole blood of delivering women show that the concentrations of mercury, lead, cobalt, arsenic and selenium in maternal and cord blood differed statistically. Lead, cobalt, arsenic and selenium appear to pass the placental barrier by a diffusion mechanism. It was also found that the mercury levels in cord blood were almost double those of the mother, suggesting that the foetus may act as a filter for the maternal mercury levels during pregnancy. Transplacental transfer for arsenic and cobalt was 80% and 45%, respectively, suggesting that the placenta modulates the rate of transfer for these elements. Cadmium, manganese, copper and zinc levels did not show statistically significant correlations between two compartments (maternal versus cord whole blood). The study confirms that most of the toxic metals measured have an ability to cross the placental barrier.